P169 Comparison of the FTD™ Urethritis Plus (7-Plex) detection kit with routine sexual health clinic nucleic acid amplification testing for detection of Neisseria gonorrhoeae and Chlamydia trachomatis in urine, vaginal, pharyngeal and rectal samples. (30th June 2016) - Harrison, Mark; Harding-Esch, Emma; Broad, Claire; Soares, Clare; Fuller, Sebastian; Okala, Sandra; Saunders, John; Barber, Tristan; Hay, Phillip; Sadiq, Syed Tariq
Abstract : Background/introduction: The FTD™ Urethritis Plus (FTDU) nucleic acid amplification test (NAAT) detects seven pathogens associated with urethritis, including Chlamydia trachomatis (CT), Neisseria gonorrhoeae (NG), Mycoplasma genitalium, Trichomonas vaginalis, Mycoplasma hominis, Ureaplasma urealyticum and Ureaplasma parvum . Aim(s)/objectives: To perform an initial diagnostic evaluation of FTDU performance for NG and CT, compared to routine clinic NAAT (BD Viper), in prospectively collected genital samples from symptomatic patients. Methods: Alongside routine clinical samples, additional samples (n = 684) were taken from symptomatic patients: females (vulvovaginal swabs; VVS), men-who-have-sex-with-women (MSW) (urine) and men-who-have-sex-with-men (MSM) (rectal and pharyngeal swabs; urine). Results: The prevalence of CT was 9.38% across sample sites tested (24 Female, 21 Male, 3 MSM Urine, 1 MSM Pharynx and 5 MSM Rectal positives). The prevalence of NG was 9.74% across sample sites tested (5 Female, 6 Male, 10 MSM Urine, 17 MSM Pharynx and 19 MSM Rectal positives). Discussion/conclusion: FTDU was accurate for detecting CT from genital sites only and had poor sensitivity for NG at all sampling sites. This test could not be used for NG testing for urine or extra genital testing without supplementary testing according to the BASHH guidelines as the PPV is below 90%. Further work is required to establish its suitability for detecting the other organisms claimed.